Determination of Flood Distribution using Post-Flood Event Measurement - Zamri, Muhammad Adib Irsyad; A Halim, Muhammad Afiq Syakirin; Idris, Muhammad Aiman Muhhafiz; Abdul Kadir, Muhammad Azraie (Multidisciplinary Applied Research and Innovation, 2024)
The determination of flood distribution is essential for understanding the extent and impact of flooding events. This study aims to determine the flood level in the Sri Medan area and develop a flood distribution map using post-flood event measurements. Additionally, this study also to analyze the causes of the flood in Sri Medan, Johor. A point measurement method was employed to gather data on flood levels in the Sri Medan area following a flood event. This involved collecting measurements at various locations within the affected region. Through the implementation of point measurement methods, the flood levels in the Sri Medan area were successfully determined. Next, a flood distribution map was successfully developed for the Sri Medan area. Lastly, the causes of the flood in Sri Medan were also successfully determined.